Anxiety and Depression Symptoms of Family Members of Intensive Care Unit Patients: A Prospective Observational Study and the Lived Experiences of the Family Members - Gurbuz, Hande; Demir, Nalan (Avicenna Journal of Medicine, 2023)
Background The aim of this study is to investigate the factors affecting symptoms of anxiety and depression in the family members of critically ill patients.Methods This prospective cohort study was conducted in an adult tertiary care mixed medical–surgical intensive care unit (ICU) at a tertiary-level teaching hospital. The symptoms of anxiety and depression of first-degree adult relatives were evaluated with the Hospital Anxiety and Depression Scale. Four family members were interviewed and asked about their experiences during the ICU process.Results A total of 84 patients and their family members were included in the study. The symptoms of anxiety were present in 44/84 (52.4%), and depression was present in 57/84 (67.9%) family members. A nasogastric tube was found to be related to anxiety (p = 0.005) and depressive symptoms (p = 0.002). The family members of the patients with an acute developed illness had 3.9 (95% confidence interval [CI]: 1.4–10.9) times the odds of having the symptoms of anxiety and 6.2 (95% CI: 1.7–21.7) times the odds of having the symptoms of depression than the family members of the patients with an illness developed on a chronic basis. The family members of the patients who died in the ICU had 5.0 (95% CI: 1.0–24.5) times the odds of being depressed than the patients discharged from the ICU. All interviewees stated having difficulty understanding and remembering what was told. The common feelings of all the interviewees were desperation and fear.Conclusions Awareness of the emotional stress of family members can help develop interventions and attitudes to alleviate symptom burden.
Keywords: anxiety; intensive care unit; critically ill; death; depression; depressive symptoms; family